Trauma and Infection Risk Factors for Stroke - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2013)
Researchers at University of California at San Francisco (UCSF); Kaiser Permanente, Oakland, CA; and University of Utah, Salt Lake City performed a casecontrol study of recent exposure to trauma or infection in 126 childhood (<19 years old) cases of arterial ischemic stroke (AIS).